2010
DOI: 10.3390/ijms11041580
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implant Systems

Abstract: Among various dental materials and their successful applications, a dental implant is a good example of the integrated system of science and technology involved in multiple disciplines including surface chemistry and physics, biomechanics, from macro-scale to nano-scale manufacturing technologies and surface engineering. As many other dental materials and devices, there are crucial requirements taken upon on dental implants systems, since surface of dental implants is directly in contact with vital hard/soft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
129
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 365 publications
(522 reference statements)
1
129
0
3
Order By: Relevance
“…25,26 The cellular behavior is also influenced by surfaces with nanotopography. Recent studies 3,27,28 have shown that surfaces with micro-and nanoscale topography are more conducive to the proliferation of bone cells and to the formation of bone of good quality and at good quantity. The complex interactions in the cell-matrix substrate and in cell signaling events have been confirmed at the nanoscale.…”
mentioning
confidence: 99%
“…25,26 The cellular behavior is also influenced by surfaces with nanotopography. Recent studies 3,27,28 have shown that surfaces with micro-and nanoscale topography are more conducive to the proliferation of bone cells and to the formation of bone of good quality and at good quantity. The complex interactions in the cell-matrix substrate and in cell signaling events have been confirmed at the nanoscale.…”
mentioning
confidence: 99%
“…19. Anodized dental implant surface, showing volcano shaped saliencies As Oshida et al (Oshida et al, 2010) oxides formed on Ti materials are varied with a general form; TiOX (1 < x < 2). Depending on x values, there are five different crystalline oxides; i.e., (1) cubic TiO (ao = 4.24 Å), (2) hexagonal Ti2O3 (ao = 5.37 Å, = 56°48'), (3) tetragonal TiO2 (anatase) (ao = 3.78Å, co = 9.50 Å), (4) tetragonal TiO2 (rutile) (ao = 4.58 Å, co = 2.98 Å), and (5) orthorhombic TiO2 (brookite) (ao = 9.17 Å, bo = 5.43 Å, co = 5.13 Å).…”
Section: Sandblasting Surface Treatmentmentioning
confidence: 99%
“…Functionality and durability depend on the bulk properties of the material, whereas biological response is governed by the surface chemistry, surface topography, surface roughness, surface charge, surface energy, and wettability (Oshida et al, 2010). The implants biocompatibility has been shown to depend on relationship with biomaterials, tissue, and host factors, being associated with both surface and bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium materials (commercially pure titanium ASTM Grades 1 through 4 or Ti-based alloys) are considered to be the most biologically compatible materials to vital tissue (Oshida et al, 2010). Their more recent applications are in maxillofacial, oral and cardiovascular-surgery, as well as in orthopaedics indicating a superiority of titanium materials compared to stainless steel, Co-Cr-Mo alloys (Kasemo, 1983).…”
Section: Introductionmentioning
confidence: 99%